Shahatra (F.parviflora Lam)- a comprehensive review of its ethnopharmacology, phytochemistry and pharmacology. (25th March 2022) - Jamaldeen, F.N.; Sofi, Ghulamuddin; Fahim, M.F.M.; Aleem, Mohammed; Begum, E.M.G.K.N.
Abstract: Ethnopharmacological relevance: F.parviflora Lam. is a plant widely used in traditional medicine systems like Unani, Ayurveda, and folk medicines in Iraq and Turkey. It is known as Shahatraj in Arabic, which is derived from Shahatra and called Shajaratuddam . In the ancient Unani system, it is called Shajaratuddam . The term derived from Sajarat means tree, and Dam means blood since it has a potent blood purifier property. Aim of the study: This review focused on comprehensive, updated information on the F.parviflora Lam . about the traditional uses, phytochemical and pharmacology and provided insights into potential opportunities for future research. Materials and methods: The classical literature of Shahatra for its temperament ( Mizaj ), medicinal properties and traditional therapeutic uses were gathered from nearly 15 classical Unani books, eight local and foreign books on ethnomedicines and ethnobotany in English. The information of pharmacognosy, phytochemical and pharmacological activities of F.parviflora Lam was collected by browsing the Internet (PubMed, ScienceDirect, Wiley online library, Google Scholar, ResearchGate). The relevant primary sources were probed, analysed, and included in this review. The keywords used to browse were F.parviflora Lam, shahatra, pitpapda, and fine fumitory. Relevant Sources were gathered up to April 2021, and the chemical structures were drawn using Chemsketch software. The species name was checked with http://www.theplantlist.org (" F.parviflora Lam. — The Plant List, " n.d.). The materials published in both Urdu and English were included in the review. Results: F.parviflora Lam was found to possess an excess of bioactive compounds and broad pharmacological properties, including antimicrobial activity, antioxidant activity, antiprotozoal activity, anthelmintic activity, antidiarrheal, antispasmodic and bronchodilator activities, antidiabetic activity, hepatoprotective activity, anticancer activity (cytotoxicity)of nanoparticle, antipruritic activity, dermatological effect, reproductive effect, anti-inflammatory and anti-nociceptive activity. Conclusion: In this review, the botany, traditional uses, phytochemistry and pharmacology of F.parviflora were reviewed . It showed a broad scope of application, and its benefits had been extended far beyond the initial conventional uses of its parts. It consists of numerous chemical constituents and reported various pharmacological activities such as antimicrobial activity, antioxidant activity, antidiabetic activity, hepatoprotective activity, anticancer activity etc. Though it is widely studied using several in-vitro and in-vivo models and tested clinically for skin diseases, several gaps and research priorities have been identified that need to be addressed in the future, such as active ingredients and their mechanism of action applications in immunomodulation and hepatic diseases. Graphical abstract: Image 1